Targeting the T-cell co-stimulatory CD27/CD70 pathway in cancer immunotherapy: rationale and potential. (July 2015) - van de Ven, Koen; Borst, Jannie
In 2013, cancer immunotherapy was named 'breakthrough of the year' based on the outcome of clinical trials with blocking antibodies to the T-cell co-inhibitory receptors CTLA-4 and PD-1. This success has emphasized that cytotoxic T-cell responses to cancer can occur, but are limited by peripheral tolerance and by immunosuppression in the tumor microenvironment. Targeting of CTLA-4, PD-1 or its ligands partly overcomes these limitations and can now be applied in multiple immunogenic cancer types. Furthermore, an increased success rate is expected from combining CTLA-4 and/or PD-1 blocking with deliberate engagement of T-cell co-stimulatory receptors, particularly TNF receptor (R) family members. The TNFR family includes CD27 (Tnfrsf7), for which an agonistic antibody has recently entered clinical trials. In this review, we describe how CD27 co-stimulation impacts the T-cell response, with the purpose to illuminate how CD27 agonism can be exploited in cancer immunotherapy.